Fear of Failure and Quarter-Life Crisis Among Final-Year Education Students: Evidence from Tadulako University - Wafik Saskia; Munifah Munifah; Ikhlas Rasido; Dhevy Puswiartika (MASI Mandiri Edukasi, 2025)
This study aims to describe the levels of fear of failure and quarter-life crisis and to determine whether there is a relationship between fear of failure and quarter-life crisis among final-year students majoring in Education at Tadulako University. The population in this study consisted of 774 final-year students majoring in Education at Tadulako University in the 2022 cohort, and the research sample comprised 89 students, as determined by the Slovin formula. Simple random sampling was used to collect the sample. Pearson’s product-moment correlation was used to analyse the data in this study. The results of the analysis indicate that the fear of failure falls into the low category, with 36% (32 students), while the quarter-life crisis is categorized as high, with 38% (34 students). The correlation coefficient reveals a significant positive relationship between the fear of failure behaviour and the quarter-life crisis (r = 0.766, p < 0.05), indicating that as the fear of failure behaviour increases, the quarter-life crisis also increases, and vice versa.